Metanephric stromal tumor: An unusual pediatric renal neoplasm - Sunil K Bajaj; Ritu Misra; Vineeta Batra; Rohini Gupta; Deepak Bagga (Wolters Kluwer Medknow Publications, 2013)
A renal tumor in a 14-month- old child, who was initially diagnosed as mesoblastic nephroma, but on review post surgery was diagnosed as hyper-differentiated metanephric stromal tumor, with its excellent prognostic outcome. An attempt is made to document imaging features that may enable one to suspect this rare condition. The literature is reviewed with emphasis on its distinction from its look-alikes in the pediatric age group.